Experimental Study on the Performance of an Air Conditioning Unit with a Baffled Indirect Evaporative Cooler - Seong-Bhin Kim; Kwang-Am Moon; Hwi-Ung Choi; Kwang-Hwan Choi (Energies, 2024)
Indirect evaporative coolers (IECs) use the latent heat of water evaporation to cool air. This system has the advantage of operating at low power without a compressor and does not increase the absolute humidity of the air. However, an IEC is difficult to use on its own because its cooling capacity is limited by the theoretical constraint of the wet-bulb temperature of the ambient air. Therefore, an air conditioning unit (ACU) was integrated with an IEC and experimentally evaluated in this study. The dry and wet channels of the IEC were integrated with an ACU evaporator and a condenser, unlike previous studies where IECs were integrated solely with either an evaporator or a condenser. This reduced the cooling load on the evaporator and helped the condenser to dissipate heat to improve the performance of the existing ACU. In addition, the IEC was equipped with baffles to improve its performance. To assess the extent of the performance improvement due to integration with the IEC, comparisons were also performed under the same experimental conditions with an ACU only. The results showed that under conditions with an indoor temperature of 32 °C, integrating the IEC with the ACU increased the average cooling capacity by 13.1% and decreased the average power consumption by 8.60% during the test period, compared to using only the ACU. Consequently, the average coefficient of performance (COP) increased by 19.5% compared to using only the ACU under the same conditions.